Effect of friction stir welding parameters on fatigue resistance, weld quality and mechanical properties of Al 6061-T651 / Mohamed Ackiel Mohamed and Yupiter HP Manurung - Mohamed, Mohamed Ackiel; Manurung, Yupiter Hp (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
The present work examined the fatigue life cycle, tensile behavior, nugget zone hardness and weld quality of friction stir welded Al 6061-T651 with varying welding parameters. The joining process was conducted with varied process parameters namely the rotational speed and traverse speed on butt joints with plate thickness of 6mm. The experimental method was based on a full factorial design with varied parameters between 350-1400 rpm and 0.2-4.6 mm/s for rotational speed and traverse speed respectively utilizing four levels for each parameter. The fatigue life cycle for each variation was determined. The zone formation and internal weld defects were analyzed using digital x-ray and macroscopically with a designated weld class for each parameter variation. Furthermore, the causes of internal weld defects and the effect of zone formation on tensile strength properties and hardness profile were discussed and concluded. The best mechanical properties are obtained at higher traverse speeds with moderate rotational speed probably owing to the incidence of homogeneous grains and higher heat input. Two parameter variations displayed a combination of good weld class quality and mechanical properties namely rotation speed 950rpm with 4.6 mm/s traverse speed as well as 650 rpm rotation speed with 2.4 mm/s traverse speed. An increase in the nugget hardness shows an increment in the fatigue life.